2005
DOI: 10.1017/s0140525x05410079
|View full text |Cite
|
Sign up to set email alerts
|

Altered sensitivity to reward in children with ADHD: Dopamine timing is off

Abstract: despite general agreement that altered reward sensitivity is involved in attention-deficit/hyperactivity disorder (adhd), a wide range of different alterations has been proposed. we cite work showing abnormal sensitivity to delay of reward, together with abnormal sensitivity to individual instances of reward. we argue that at the cellular level these behavioural characteristics might indicate that dopamine timing is off in children with adhd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…The present findings clearly show, however, that motivational incentives were effective in enhancing electrophysiological markers of inhibitory control in ADHD, although the effects were not differentially greater than in control subjects. This suggests first that, in support of previous studies, the ADHD children were neither hypersensitive nor hyposensitive to these immediate, consistent incentives ( 12 ) and second that, to achieve the same level as control children in both the baseline and motivated conditions, children with ADHD may require incentives that differ quantitatively or qualitatively from those that produce effects in typically developing children. It will therefore be important in future research to investigate other factors that influence the effectiveness of incentives on inhibitory control in ADHD, such as reward magnitude, reinforcement history, and reinforcement scheduling ( 11,12 ).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The present findings clearly show, however, that motivational incentives were effective in enhancing electrophysiological markers of inhibitory control in ADHD, although the effects were not differentially greater than in control subjects. This suggests first that, in support of previous studies, the ADHD children were neither hypersensitive nor hyposensitive to these immediate, consistent incentives ( 12 ) and second that, to achieve the same level as control children in both the baseline and motivated conditions, children with ADHD may require incentives that differ quantitatively or qualitatively from those that produce effects in typically developing children. It will therefore be important in future research to investigate other factors that influence the effectiveness of incentives on inhibitory control in ADHD, such as reward magnitude, reinforcement history, and reinforcement scheduling ( 11,12 ).…”
Section: Discussionsupporting
confidence: 72%
“…Children with ADHD also show atypical regulation of motivational state: they respond to rewards when they are delivered immediately and with regularity but are less sensitive to rewards that are delayed or intermittent ( 11,12 ). It has been suggested that deficits in higher cognitive functions in ADHD, including response inhibition, conflict processing, and attention, are a consequence of impairments in the self-regulation of arousal and motivational state ( 13,14 ).…”
mentioning
confidence: 99%
“…Also, ADHD is a risk factor for heavy alcohol use and initiation of illicit drug use in young adults (Vogel et al, 2016). Some studies have suggested that this increased risk can be explained by shared genetics (Capusan, Bendtsen, Marteinsdottir, Kuja-Halkola, & Larsson, 2015; Edwards & Kendler, 2012), while psychological factors may also contribute to enhance the risk for substance use: (emotional) impulsivity (De Alwis, Lynskey, Reiersen, & Agrawal, 2014; Pedersen et al, 2016; Roberts, Peters, Adams, Lynam, & Milich, 2014) and aversion to delay gratification (Wickens & Tripp, 2005) as well as neuroticism and anxiety (Davis, Cohen, Davids, & Rabindranath, 2015) may mediate between ADHD symptoms and early inclination toward substance use.…”
Section: Introductionmentioning
confidence: 99%
“…Other research has indicated that the positive relationship between nicotine and marijuana use and ADHD-symptom dimensions may also be mediated by aspects of impulsivity ( 28 ). In addition, related investigations have found that an aversion to delayed gratification and an abnormal sensitivity to individual instances of reward are mediating links between symptoms of ADHD and addictive behaviors ( 29 ). These authors have suggested that a high reward drive might imply that “dopamine timing is off” in those with ADHD.…”
Section: Introductionmentioning
confidence: 99%